PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP KREDIT PERBANKAN DI INDONEIA - B01111122, Liliana Christina (Jurnal Curvanomic, 2015)
The title of this research is the effect of economic growth and inflation onbank credit in Indonesia. This reseach aims to determine the effect of economicgrowth in Indonesia and to determine the effect of inflation on bank credit rate inIndonesia in 1984 to 2013. This research uses descriptive quantitative method byusing multiple linear regression model with Ordinary Least Square method (OLS),as well as statistical analysis tools that is determination (R2), F test and t test totest the hypothesis whether economic growth and inflation effect on bank creditThese results indicate that the negative effect on economic growth bycoefficient -0.247681 and significant, while the effect of negative inflation ofcoefficient -5.38E-05 and not significant to the bank credit in Indonesia. Thecoefficient of determination value by 0.743235, which means the amount ofinfluence exerted by the variable economic growth and inflation on bank credit inIndonesia at 74%, while the remaining 26 percent are influenced by other factorssuch as income, interest rates and unemploymentKeywords: Economic Growth and Inflation Effect on Credit Banking